Releaser Design and Schedulability Analysis for Care-Taking Tasks in Real-Time Systems - Hölscher, Nils; Heider, Kay; von der Brüggen, Georg; Günzel, Mario; Chen, Kuan-Hsun; Chen, Jian-Jia (2026 IEEE 32nd Real-Time and Embedded Technology and Applications Symposium (RTAS))

Kulturkonservatismus-Geistesaristokratie-Ressentiment. Rechte Intellektuellendiskurse zwischen Ästhetik und Weltanschauung seit 1918

Representation theory of the Gelfand quiver and Harish-Chandra modules for SL_2(R) - Burban, Igor; Gnedin, Wassilij (arXiv:2604.00274)
In 1970, Gelfand posed the problem of classifying the indecomposable objects in a representation category equivalent to the principal block of Harish-Chandra modules for $\mathsf{SL}_2(\mathbb{R})$; explicit solutions were obtained by Bondarenko, and, independently, Crawley-Boevey. In this article, we give a complete answer to Gelfand's problem from a derived category perspective. We classify indecomposable objects in the bounded derived category of nilpotent representations of the Gelfand quiver in terms of band and string complexes, and determine their images under the derived Auslander-Reiten translation, the sign involution, and the contragredient duality. The four main combinatorial classes are characterized in Lie-theoretic as well as homological terms. For the abelian category of nilpotent representations, we provide projective resolutions, standard homological invariants and explicit representation matrices of all indecomposables. Our approach can be extended to arrow ideal completions of path algebras of skew-gentle quivers.

Volume 71.2 (2026) - Hartmann, Alexandra; Purk, Antonia (Amerikastudien/American Studies)

Representation theory of the real Gelfand order and real Harish-Chandra modules for SL_2(R) - Burban, Igor; Drozd, Yuriy (arXiv:2605.18000)
In this article we study the principal block of the category of real Harish-Chandra modules for the group $\mathsf{SL}_2(\RR)$ and relate it to the category of finite dimensional modules over the so-called real Gelfand order. We describe several distinguished classes of the corresponding indecomposable representations.

Vitamin D, inflammation and depressive symptoms in adolescents: analysis using observational and interventional data - Schlarbaum, Laura; Jankovic, N.; Engler, H.; Hirtz, R.; Grasemann, C.; Peters, T.; Hinney, A.; Antel, J.; Hebebrand, J.; Föcker, M.; Libuda, Lars (Neuroscience Applied)

Indefinite causal order in cavity quantum electrodynamics - Castaños-Cervantes, Luis Octavio; Procopio Peña, Lorenzo Manuel; Bartley, Tim J. (Physical Review Research)
Indefinite causal order (ICO) has the potential to be a new resource for quantum information processing. In most of its experiments, ICO has been investigated in a photonic platform. Here, we investigate ICO in a cavity quantum electrodynamics system composed of two cavities. Our results show that ICO can create highly entangled states of two distant cavity fields that never interact directly independent of the initial (excited or ground) state of the atom. These entangled states can have the form of one- or two-photon NOON states. We show that ICO can interchange one photon between both cavities without changing the state of the atom, something that is impossible to achieve for two cavities in well-defined order. Furthermore, the vacuum Rabi oscillations either disappear or lose their sinusoidal form with ICO. Our results show the potential that ICO can offer in the paradigm of light-matter interaction for coherently controlling atom-field observables.

Bildungstechnologie in der schulischen Bildung - Herzig, Bardo (The Age of EdTech: Bildungstechnologie im Spannungsfeld zwischen Innovation und Qualität)

Source Code-Driven GDPR Documentation: Supporting RoPA with Assessor View - Khedkar, Mugdha; Schlichtig, Michael; Bodden, Eric (IEEE International Conference on Software Analysis, Evolution and Reengineering (SANER))

The spatial and sectoral incidence of Germany’s COVID-19 insolvency gap - Rahali, Mahdi; Kosi, Urska; Gassen, Joachim

From Avatar Cues to Pseudonymity Modes: Identity Perception in Social Virtual Reality - Tölle, Laura; Rose, Robert; Trier, Matthias

Semi-homogeneous vector bundles on abelian varieties: moduli spaces and their tropicalization - Gross, Andreas; Kaur, Inder; Ulirsch, Martin; Werner, Annette (Moduli)
Abstract Let $A$ be an abelian variety with totally degenerate reduction over a non-Archimedean field. We describe the moduli space of semi-homogeneous vector bundles on $A$ from the perspective of non-Archimedean uniformization and show that the essential skeleton may be identified with a tropical analogue of this moduli space. For $H=0$ our moduli space may be identified with the moduli space $M_{0,r}(A)$ of semi-stable vector bundles with vanishing Chern classes on $A$ . In this case we construct a surjective analytic morphism from the character variety of the analytic fundamental group of $A$ onto $M_{0,r}(A)$ , which naturally tropicalizes. One may view this construction as a non-Archimedean uniformization of $M_{0,r}(A)$ .

Scaling Bottom-Up IFDS Taint Analysis with Optimized Data-Flow Encoding - Schiebel, Fabian Benedikt; Bodden, Eric (40th European Conference on Object-Oriented Programming (ECOOP 2026))

Surface initiated radical-promoted cationic photo-polymerization from silica nanoparticles employing a trisacylgermanium photoinitiator - Zhang, Zizheng; Müller, Matthias W.; Schmallegger, Max; Paris, Matthias; Haas, Michael; Gescheidt, Georg; Gutmann, Torsten; Griesser, Thomas; Kern, Wolfgang; Bandl, Christine (European Polymer Journal)

Static Analysis Traces can Help Dynamic Symbolic Execution: a Replication Study - Kummita, Sriteja; Schiebel, Fabian Benedikt; Bodden, Eric; Miao, Miao; Wei, Shiyi (2026 IEEE International Conference on Software Analysis, Evolution and Reengineering (SANER))

Multicomponent Betti reaction affords covalent organic framework nanoreactor for palladium-catalyzed nitroarene reduction - Salarinejad, Neda; Dinari, Mohammad; Lins, Jonas; Gutmann, Torsten; Chae, Keun Hwa (Communications Chemistry)

Modellgestützte Optimierung eines Ultraschall-Torsionsschweißsystems - Dohmen, Markus Daniel; Bornmann, Peter; Littmann, Walter; Hemsel, Tobias; Sextro, Walter (PLUS-Elektronikfertigung)

A comprehensive numerical study of the wetting behavior in structured packings with a direct consideration of the packing microstructure - Dechert, Christopher; Riese, Julia; Kenig, Eugeny (Chemical Engineering Science)

Steuersicherheit als Standortfaktor: Planbarkeit statt Investitionshemmnis - Sureth, Caren (Betriebs-Berater)

Verstehen adressieren und Darstellungen vernetzen: Exemplarische Aufgaben zur analytischen Geometrie - Herrmann, Janine; Hoffmann, Max; Wessel, Lena (Mathematikabitur „Status Quo – Quo Vadis“: Tagungsband zur Fachtagung zum Mathematikabitur am 11./12. Februar 2025 in Dresden)
Keywords: Verstehensorientierung; Darstellungsvernetzung; analytische Geometrie; Abitur; Aufgabenentwicklung; Lehrkräfteprofessionalisierung